Association between dietary vitamin K intake and lipid metabolism among populations with cardiovascular disease - Liu, Tao; Wang, Lili; Dai, Qiming; Pan, Yesheng (Frontiers in Nutrition, 2025)
BackgroundThe objective of this investigation was to examine the correlation between intake of dietary vitamin K and lipid metabolism in cardiovascular disease populations.MethodsThe data for this investigation were obtained from the National Health and Nutrition Examination Survey (NHANES) 2003–2014. The exposure variable was the total daily intake of dietary vitamin K (μg). Triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) comprised the lipid indicators. To investigate the relationship between vitamin K intake and lipid metabolism, the following analyses were conducted: weighted multiple linear regression, smoothing curve fitting, generalized additive models, threshold analysis, subgroup analysis, and sensitivity analyses.ResultsUltimately, 1,543 participants aged 18 years or older were enrolled. The total daily intake of dietary vitamin K was found to be negatively correlated with TG (β: −15.57, 95% CI: −27.806, −3.333) and TC (β: −6.564, 95% CI: −12.252, −0.877). For each 1 ug increase in the total daily intake of dietary vitamin K, the LDL-C would decrease by 0.510 mg/dl (95% CI: −0.940, −0.078) when the total daily intake of dietary vitamin K was less than 23.7 ug. HDL-C was not influenced by total daily intake of dietary vitamin K. Furthermore, subgroup analyses and sensitivity analyses revealed that an increase in the total daily intake of dietary vitamin K was still negatively associated with TG, TC, and LDL.ConclusionThe consumption of foods with high vitamin K levels might contribute to the improvement of TC, TG, and LDL-C levels in CVD populations.